2015
DOI: 10.1039/c4cy00822g
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of the Mn–Na2WO4/SiO2 catalytic system for the oxidative coupling of methane in a fluidized-bed reactor

Abstract: The catalytic system Mn–Na2WO4/SiO2, was studied in a miniplant fluidized-bed reactor for oxidative coupling of methane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 39 publications
6
30
0
Order By: Relevance
“…C 2 yield varies with every parameter of the reaction conditions. The C 2 yields are consistent with previously reported yields obtained using Mn‐Na 2 WO 4 catalysts under similar reaction conditions including the artificial neural network results, where the C 2 yields of 22 % reported in this work are consistent with C 2 yields of 23 % previously reported using artificial neural network . Given the nature of the random forest regression model, the impact of the descriptors are also further evaluated.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…C 2 yield varies with every parameter of the reaction conditions. The C 2 yields are consistent with previously reported yields obtained using Mn‐Na 2 WO 4 catalysts under similar reaction conditions including the artificial neural network results, where the C 2 yields of 22 % reported in this work are consistent with C 2 yields of 23 % previously reported using artificial neural network . Given the nature of the random forest regression model, the impact of the descriptors are also further evaluated.…”
Section: Resultssupporting
confidence: 90%
“…The C 2 yields are consistent with previously reported yields obtained using Mn-Na 2 WO 4 catalysts under similar reaction conditions including the artificial neural network results, where the C 2 yields of 22 % reported in this work are consistent with C 2 yields of 23 % previously reported using artificial neural network. [23,29,30,31] Given the nature of the random forest regression model, the impact of the descriptors are also further evaluated. During data acquisition, a reaction parameter value is changed until C 2 yield reaches a local maximum or a plateau value as long as the variable parameter is within safety limits of the experiment (e. g. explosion limits); meanwhile, the other parameter values are kept constant.…”
Section: Resultsmentioning
confidence: 99%
“…The 2% loss contains them as well) and it was also sieved by 350 µm sieve and the percentage of the particles smaller than this range, in compare with the fresh catalyst, was 4%, therefore it can be concluded that the attrition was negligible. There was no agglomeration observed during the experiment which is expected to be one of the major problems of this catalyst in OCM fluidized-bed reactor [11]. In all experiments discussed in this work, as well as this stability test, the thermocouple inside the reactor showed an isothermal catalyst bed with having maximum 5 °C temperature difference between first 5 or 6 measuring points which are every 2 cm along the reactor.…”
Section: Stability Testmentioning
confidence: 95%
“…%] at 2.2%, which is lower than the composition reported by Fang et al [4]. This composition was chosen due to catalyst bed defluidization issues described in previous study [11].…”
Section: Introductionmentioning
confidence: 94%
“…The Eley-Rideal mechanism states that the reaction between gaseous methane and adsorbed oxygen, either dissociative [58][59][60]66] or molecularly type [61,62], is the rate limiting step (RLS) in OCM reactions. An exemplary catalyst for this mechanism is 5%Na 2 WO 4 -2%Mn/SiO 2 [54,[67][68][69][70]. The Langmuir-Hinshelwood mechanism regards RLS as the reaction between adsorbed methane and oxygen species.…”
Section: Reaction Pathways Of Ocm Reactions Over Hap-based Catalystsmentioning
confidence: 99%